2015
DOI: 10.1007/s11192-015-1775-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in research performance and its impact on careers: a longitudinal case study

Abstract: We take up the issue of performance differences between male and female researchers, and investigate the change of performance differences during the early career. In a previous paper it was shown that among starting researchers gendered performance differences seem small to non-existent (Van Arensbergen et al. 2012). If the differences do not occur in the early career anymore, they may emerge in a later period, or may remain absent. In this paper we use the same sample of male and female researchers, but now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 50 publications
2
85
0
8
Order By: Relevance
“…This gender disparity in citations is consistent with several studies across disciplines, 14,32,3537 although reasons for such a disparity remain unclear 2,4,38 . Unlike many studies in other fields that did not consider seniority, this study accounted for confounding due to seniority 37 and still found similar results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This gender disparity in citations is consistent with several studies across disciplines, 14,32,3537 although reasons for such a disparity remain unclear 2,4,38 . Unlike many studies in other fields that did not consider seniority, this study accounted for confounding due to seniority 37 and still found similar results.…”
Section: Discussionsupporting
confidence: 89%
“…1 Women scientists also tend to publish fewer last-author articles than men and accrue fewer citations per publication, 24 though the pattern varies by scientific field and geographic region. 5 …”
Section: Introductionmentioning
confidence: 99%
“…[9] The first conclusion remains when using the new data; however, the second not, as it was based exactly on the patterns in the top of the performance: with the original dataset, slightly more women were in the top of the performance distribution, but this was not the case anymore with the corrected data (note 5). [10] We also show the graphs for the error in the citation counts [ Figures 3 and 4]. Here, we find a similar pattern as with publications: a few overestimated applicants and a few strongly underestimated (successful) applicants.…”
Section: Analyzing the Errorsupporting
confidence: 79%
“…In a 2004 survey women were awarded just 36% of science PhDs, 33% of junior faculty positions, and 11% of tenured senior faculty slots in Europe. An international survey found that women in medical and science academia were far less likely than male peers to become full or associate professors (60% of appropriately trained men versus 31% of women) 4. And women were more likely to fill lower status academic slots: “researcher,” assistant professor, or adjunct teaching positions (about 38% of men in total versus 63% of women).…”
Section: Early Career Access To Education and Appointmentsmentioning
confidence: 99%